2005
DOI: 10.3171/jns.2005.102.3.0547
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of life-threatening refractory emesis to gabapentin—scopolamine therapy following posterior fossa surgery

Abstract: Craniotomy-associated chronic emesis can be refractory to currently approved antiemetic therapy. The authors describe a man who suffered 4 weeks of severe refractory emesis, failure to thrive, and a 40-lb weight loss after he underwent resection of a posterior fossa cholesteatoma. The patient experienced complete resolution of emesis and anorexia in response to combined gabapentin-scopolamine therapy. This case provides anecdotal evidence for the use of gabapentin-scopolamine therapy in patients with chronic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Gabapentin, a γ-aminobutyric acid analog has been shown to be efficacious in preventing postoperative nausea and vomiting in multiple randomized controlled trials. (Guttuso, 2014) There is also some use of gabapentin in preventing acute and delayed chemotherapy-associated nausea and vomiting, hyperemesis gravidarum, and lifethreatening refractory emesis following posterior fossa surgery [Guttuso et al 2003[Guttuso et al , 2005Ajori et al 2012;Guttuso, 2014]. It is suggested that the mechanism of action involves mitigation of calcium currents in areas such as area postrema [Guttuso et al, 2003;Guttuso, 2014].…”
Section: Novel Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gabapentin, a γ-aminobutyric acid analog has been shown to be efficacious in preventing postoperative nausea and vomiting in multiple randomized controlled trials. (Guttuso, 2014) There is also some use of gabapentin in preventing acute and delayed chemotherapy-associated nausea and vomiting, hyperemesis gravidarum, and lifethreatening refractory emesis following posterior fossa surgery [Guttuso et al 2003[Guttuso et al , 2005Ajori et al 2012;Guttuso, 2014]. It is suggested that the mechanism of action involves mitigation of calcium currents in areas such as area postrema [Guttuso et al, 2003;Guttuso, 2014].…”
Section: Novel Therapiesmentioning
confidence: 99%
“…(Guttuso, 2014) There is also some use of gabapentin in preventing acute and delayed chemotherapy-associated nausea and vomiting, hyperemesis gravidarum, and life-threatening refractory emesis following posterior fossa surgery [Guttuso et al . 2003, 2005; Ajori et al . 2012; Guttuso, 2014].…”
Section: Managementmentioning
confidence: 99%
“…6 There is a case report on the satisfactory effect of gabapentin-scopolamine therapy in an adult patient who underwent posterior fossa cholesteatoma resection and subsequently suffered from severe refractory chronic emesis. 13 From our report, gabapentin may be used in treating post-craniotomy vomiting in pediatric patients with posterior fossa tumor.…”
Section: Discussionmentioning
confidence: 82%